HOTs-Based Questions Preparation Strategy on Senior High School's Linear Programme - Yulitya, Agnes; Siregar, Mia Rizki Idaroyanni; Sembiring, Nurul Hidayah (International Journal Labs, 2021)
Background: One of the changes in the education assessment system in Indonesia today is the implementation of HOTs (Higher Order Thinking Skills) based assessments. The application of HOTs-based assessment aims to make the learning processe specially mathematics able to encourage students to develop creative thinking skills. Aim: In this article, it examines conceptually with the aim of providing educators with knowledge about the concepts, characteristics, and strategies for preparing HOTs questions. Method: This research includes qualitative descriptive research. Findings: The strategies for compiling HOTs questions are (1) Analyzing the basic competencies that will be made about HOTs; (2) Arranging a grid of questions; (3) Using interesting problems in everyday life; (4) Writing questions; and (5) Make assessment guide lines and answer keys.